KEBOCORAN TEPI RESIN KOMPOSIT BULK FILL SETELAH APLIKASI BAHAN DESINFEKSI KAVITAS CHLORHEXIDINE DIGLUCONATE 2% DAN ALKOHOL 70% - Study In Vitro - Atiek Amalia Ahsanti; Arlina Nurhapsari; M. Dian Firdausy (Odonto : Dental Journal, 2019)
Background: Caries is a form of tooth decay that is often encountered in daily life. Caries development can be prevented by dental restoration treatments. One such dental restorative material is a bulk fill composite resin with a low shrinkage level. Disinfection is needed to be done before the application of composite restorative materials. The purpose of this research was to know whether there is an microleakage of bulk fill composite resin after application of cavity disinfectionmaterial such as chlorhexidine digluconate 2% and alcohol 70%.Method: This was an experimental research with post test only control group design. The sample of research were 20 premolar teeth. The samples were divided into two groups (10 teeth each group). Group I was applied chlorhexidine digluconate 2% while group II was applied 70% alcohol. Microleakage were measured by observing a methylene blue 2% penetration depth using a metallography microscope.Result: The result indicated the significant differences microleakage of bulkfill composite resin after application of cavity disinfection chlorhexidine digluconate 2% and alcohol 70% from Mann-whitney test 0,039 (<0,05).Conclusion: Microleakage of the bulk fill composite resin was greater in the 70%alcohol than in the chlorhexidine digluconate 2%.